Tool life estimation model based on simulated flank wear during high speed hard turning - Adesta, Erry Yulian Triblas; Al Hazza, Muataz Hazza Faizi; Riza, Muhammad; Agusman, Delvis; Rosehan, Rosehan (EuroJournals Publishing, Inc., 2010)
The aim of this research is to develop a new model for estimating tool life during high speed hard turning based on the relationship between the flank wear progress and time. During high speed hard turning the dominating basic wears in the flank land are abrasive, adhesive, and diffusive. For that reasons the estimation of tool life should be based on these three basic wears. A direct estimation method was used for modeling the flank wear based on the volume loss due to abrasive, adhesive and diffusive wears in turning hard materials with higher utting speed by using ceramic cutting tool. A Matlab simulink model was developed to simulate the tool life based on the flank wear rate.